BIOREMEDIATION OF CYANIDE AND BIOFLOCCULATION ON SUSPENDED SOLIDS FROM GOLD MINING INDUSTRY USING LYSINIBACILLUS FUSIFORMIS STRAIN SKC-8 - Rizka Kurniawati, Syafira
Most of the gold processing in Indonesia is still carried out by the cyanidation process. The cyanidation process is a leaching process using sodium cyanide (NaCN). This process is considered effective and economical to process gold ore so that this process is widely used in the mining and gold extraction industries. However, among the advantages of the cyanidation process, the cyanide process can have a negative impact on the environment, especially waters as a result of the release of toxic cyanide compounds. To prevent this, it is necessary to carry out a cyanide destruction process before it can be discharged into the environment. In addition to the toxic concentration of cyanide, slurry tailings also contain suspended particles (TSS). Suspended particles are very difficult to settle naturally. Therefore, the process of adding chemicals in the form of coagulants and flocculants is required. However, the continuous consumption of chemical compounds causes the cost for the chemical destruction process and TSS removal to be relatively more expensive. Therefore, alternative reagents are needed so that the use of chemicals can be reduced, namely by using microorganisms. Besides being more economical, the use of microorganisms is also more environmentally friendly. A series of experiments were carried out to optimize the cyanide biodegradation and TSS bioflocculation processes. The experiment started with the selection of bacteria which initially numbered 65 strains to 5 strains using the cyanide agar method. After the selection of bacteria, the selection of bacterial growth media was carried out. Selection of growth media was carried out using the growth curve and emulsification index (E24) method. Preliminary experiments were carried out to determine the optimum residence time to degrade cyanide and precipitate TSS until it reached the target, namely cyanide concentration of less than 0.5 ppm and TSS concentration of less than 200 ppm. Core experiments were carried out to determine the optimum process conditions so that the cyanide degradation rate and the fastest TSS deposition rate were obtained. Variations used in the experiment were the type of bacteria, percent of bacterial inoculum, The results of the research conducted, the most optimal bacteria in degrading cyanide and precipitating TSS was Lysinibacillus fusiformis strain SKC-8 with 15% inoculation percent using SKC-1 growth media with a composition of 15 gpl molasses and seawater. The cyanide degradation rate was 0.01 ppm/hour and the TSS deposition rate was 6.067 ppm/minute with an observation time of 8 hours. At that time, the cyanide concentration and TSS concentration had met the environmental quality standards.